Bioactive polyketides and meroterpenoids from the mangrove-derived fungus Talaromyces flavus TGGP35 - Cai, Jin; Zhou, Xueming; Wang, Bin; Zhang, Xuelong; Luo, Mengyao; Huang, Longtao; Wang, Ruoxi; Chen, Yonghao; Li, Xiaoyang; Luo, Youping; Chen, Guangying; Cao, Fei; et al. (Frontiers in Microbiology, 2024)
Six new polyketides, which includes three new lactones (talarotones A–C) (1–3), one new polyketide (talarotide A) (4), two new polyenes (talaroyenes A, B) (5, 6), together with one new meroterpenoid (talaropenoid A) (7) and 13 known compounds (8–20) were isolated from the mangrove-derived fungus Talaromyces flavus TGGP35. The structure and configuration of the compounds 1–7 were elucidated from the data obtained from HR-ESI-MS, IR, 1D/2D NMR spectroscopy, Mo2 (OAc)4-induced electronic circular dichroism (ECD), CD spectroscopy, and modified Mosher's method. Compounds 5 and 20 displayed antioxidant activity with IC50 values of 0.40 and 1.36 mM, respectively. Compounds 3, 6, 11, 16, and 17 displayed cytotoxic activity against human cancer cells Hela, A549, and had IC50 values ranging from 28.89 to 62.23 μM. Compounds 7, 10–12, and 14–18 exhibited moderate or potent anti-insect activity against newly hatched larvae of Helicoverpa armigera Hubner, with IC50 values in the range 50–200 μg/mL. Compound 18 showed antibacterial activity against Ralstonia solanacearum with the MIC value of 50 μg/mL.